Life history and migration patterns of Arctic Char (Salvelinus alpinus) and Dolly Varden (Salvelinus malma malma) in the Coppermine River and Coronation Gulf - Smith, Rosie (University of Waterloo, 2025)
Arctic Char (Salvelinus alpinus) and Dolly Varden Char (Salvelinus malma malma) are of vital importance to Indigenous communities in Arctic Canada. Both species are facultatively anadromous and anadromous individuals exhibit remarkable diversity in migration tactics. Both species are also iteroparous and relatively long-lived, which allows migration patterns of individuals to be studied over multiple years. The Coppermine River, near Kugluktuk, Nunavut, is the only freshwater location where anadromous individuals of both Arctic Char and Dolly Varden have been confirmed to occur in sympatry, thereby providing a unique opportunity to compare habitat use and migration patterns between species. The overarching goal of this thesis was thus to investigate the diverse life history and migration tactics of Arctic Char and Dolly Varden that use the Coppermine River. To achieve this goal, I used an acoustic telemetry dataset from tagged Arctic Char and Dolly Varden that was collected over six years (2018–2023) in the Coppermine River and nearby marine environment of Coronation Gulf. Acoustic telemetry is widely used in aquatic environments to study animal movement, behaviour, and ecology, but many studies that employ acoustic telemetry neglect to consider the possibility that some detections may be from mortalities or expelled tags, and this can result in biased results. To assist acoustic telemetry practitioners in identifying detections from potential mortalities or expelled tags in a simple and reproducible manner, I developed the R package mort. In Chapter 2, the methods and package are described, and application is demonstrated using three diverse acoustic telemetry datasets that represent: 1) a mobile freshwater fish ((Arctic Grayling (Thymallus arcticus)) in a river network; 2) a relatively sedentary marine fish (Greenland Cod (Gadus ogac)); and, 3) a highly mobile marine fish (Atlantic Salmon (Salmo salar)). Detections flagged by mort were reviewed and removed from the acoustic telemetry datasets that were analyzed in subsequent thesis chapters (Chapter 3, Chapter 4, and Chapter 5). Marine feeding is of critical importance for anadromous Arctic Char and Dolly Varden; individuals of both species must acquire sufficient resources for growth and reproduction during the brief ice-free seasons. In Chapter 3, I used network analysis and local spatial statistics to identify and describe high use locations and movement patterns in the marine environment for char (Arctic Char or Dolly Varden; species was unknown at the time of writing) that overwintered either above or below Kugluk or Bloody Falls (“the falls”; a large cascade). Char exhibited preference for coastal habitats (relative to offshore or island habitats) and habitat use did not appear to be associated with overwintering location. Timing of return to fresh water was associated with overwintering location, however; char that overwintered above the falls returned to fresh water earlier than char that overwintered below the falls, which suggests that length and difficulty of the migratory pathway was associated with migration timing. Timing of return migration to fresh water was earlier in years when the river froze earlier; this indicates that the timing of char returning to fresh water is responsive to environmental conditions in the system. Environmental influences on timing of return migration to fresh water are largely unknown for both Arctic Char and Dolly Varden. In Chapter 4, I investigated how environmental variables were related to: 1) timing of return to fresh water by both Arctic Char and Dolly Varden; and, 2) ascension of the falls by Dolly Varden (no Arctic Char were observed ascending the falls in any year). The primary environmental cue for return to fresh water was sea surface temperature (SST); all char returned to fresh water as SST increased. Dolly Varden that overwintered above the falls returned to fresh water at colder SST (earlier) than Arctic Char and Dolly Varden that overwintered below the falls. For Dolly Varden that overwintered above the falls, river temperatures were warm and potentially stressful at the time of return. It is possible that these individuals experienced decoupling between the cue to return to fresh water (SST) and suitable conditions for migration (river temperature). Tide may have facilitated ascension of the falls but was not associated with timing of return to fresh water for Dolly Varden that overwintered above the falls. In contrast, tide was associated with timing of return to fresh water for Arctic Char and Dolly Varden that overwintered below the falls. Together, these results suggest that Dolly Varden that overwintered above the falls made directed return and upstream movements, whereas fish that overwintered below the falls returned to fresh water more passively. Differences in threshold (SST) for return migration and influence of tide between Dolly Varden that overwintered above and below the falls suggests that there may be an underlying physiological cue for migration timing and/or overwintering location. Fluvial overwintering habitats used by both Arctic Char and Dolly Varden below the falls in the Coppermine River are unusual in that there are no known groundwater inputs. In Chapter 5, I assessed evidence for several potential mechanisms that could explain overwintering below the falls: spawning status, foraging opportunities in the marine environment, and failure to ascend the falls. I found no evidence of foraging from stomach contents, although spatial and temporal coverage of samples was limited. Consistent with intent to overwinter below the falls, Arctic Char staged longer at the river mouth and moved upstream more slowly than Dolly Varden that overwintered above the falls. Dolly Varden that overwintered below the falls exhibited inconsistent movement patterns and I suggested that some Dolly Varden may thus intend to overwinter below the falls, whereas others may fail to ascend the falls. I found no confirmed evidence of spawning activity below the falls for either Dolly Varden or Arctic Char. Telemetry data indicated that Arctic Char overwintered in alternate rivers in some years, which suggests that spawning could occur in alternate rivers and that the lower reaches of the Coppermine River represent easily accessible overwintering habitat in non-spawning years. Dolly Varden that overwintered below the falls were smaller and younger than Dolly Varden that overwintered above the falls, and I suggested that it is likely that Dolly Varden migrate above the falls in spawning years. Spawning locations and frequency remain unknown for both species that use the Coppermine River. The research presented in this thesis describes the life history and migration tactics of anadromous Arctic Char and Dolly Varden that use the Coppermine River, the only freshwater system that is known to support anadromous life history types of both species. Similarities in marine habitat use and movement patterns between Arctic Char and Dolly Varden and between overwintering groups (above or below falls) of Dolly Varden may present challenges for fisheries management if conservation concerns are identified in future. I observed inter individual and inter-annual (within individual) diversity in migration tactics in Arctic Char and Dolly Varden that use the Coppermine River and Coronation Gulf, as well as influences of environmental conditions on migration timing. The observed plasticity in responses among individuals and years may promote resilience of the two species, but future research on spawning locations and spawning frequency is necessary to provide a comprehensive assessment of potential stressors that could affect the species’ persistence and inform fisheries management.   Nainaakhimayok Unipkangat (Inuinnaqtun translation of Abstract) Ikalukpiit (Salvelinus alpinus) tahapkualu Dolly Varden-mik attiktaohimayot Ikaluit ihuukit (Salvelinus malma malma) pimagioyot ikaluit nunakakaktot nikkigingmatjuk tahamani Ukkiuktaktumi Kanatami. Tahapkua tamakmik ikaluit ilangit hittuvaktut tagiokmut ilangitaok aullayuitot tattini. Ikaluit hittuvaktut tagiokmut ajikingitot iliitkuhiit hittugangamik, ilangit kakkugungugangat nammutlu hittuvaktot. Tamakmik hapkua ikaluit iglingmingni igniokpaktot kakkugungagangat tatvalu innughaakataktot, taimatot naunaiyaikatagungnaktavut kanok iliitkuhiitnik hittunahuagangata kaffiktaklugit ukkiuni. Tatvani kugluktumi Kuukmi, kanninganiitok Kugluktuk, Nunavut, tatvatuanguyok kaoyimayavut immagiktok hittuviat tahapkua ikalukpiit tatvalu tahapkua ikaluit ihuukit attiktaohimayot Dolly Varden, una Kuuk nayugagiyat attaotikut. Tukkikaktok tahamna Kuuk atjikutakangitok nayugagiyat hittuvigivakhutjuk tahapkua ikaluit. Taimatot ihomagiloaktavut tahamna naunaiyaiyot havagiyomavlutjuk kanok allangayaghaita hittuvigikatakhutjuk tahapkua ikalukpiit tatvalu hapkua Dolly Varden ikaluit ihuukit nayogagiyat tahamna Kugluktumi Kuuk. Tatva taimatot havagiyomavlutjuk, tahapkua ikalukpiit Dolly Varden ikaluit ihuukit attaataliktoktaovaktot nallauhiktokhugitlo tauktoktaovaktot namungaokatakmangata 6-sinik ukkiunik havagivlutjuk (2018-min 2023-mut) tahamani Kugluktup Kuukmi tatvalu kaningani tahamani tagiokmi Coronation Gulf-mi. Ataataktuinik tatvalu tammalaitkutinik nallauhiktoinik atogaokataktot imakmi nauyaiyaotigivlutjuk ikaluit namungauningitnik, iliitkuhiitnik tatvalu nayogagiyaitnik, kihiani ammihuyut tahapkua tammalaitkutinik nallauhiktoinik ihomagingitait immakak illangit hapkua naunaiyaotait pihimayungnakhiyat ataatakhimayunit ikalunit tukkuhimayunit uvalunin ataatait kattaktitaonikata, taimatot nallukhaotaungmiyot. Ikkayotaongmat inuknun naunaiyaiyunot ummayunik immakak tahapkua ataatait tukkuhimayuningakhimayot ikalunit uvalunin kattakhimayonik ataatanit, ihuaghaihimaliktunga naunaitkutikhamik kagitaoyakukutimik attikaktok mort-mik. Tatvani unipkat Naunaipkutani 2-mi, naunaiyakhimayaga unipkagivlugo kanok atoktaoyagiakaktok una kagitaoyakut naunaiyaotaoyok, ayogiktoitjutigiyaga kano kuna kagitaoyakut naunaiyaotaoyok atoktaoyungnaktok pingahut allatkit naunaipkutini: 1) tattiniotak una ikaluk (Hulukpaugak (Thymallus arcticus)) kukanikataktok; 2) tagiokmiotak ikaluk una hangukatangitok (Uugak (Gadus ogac)); tatvalu, 3) ungahiktoliakataktok una tagiokmiotak ikaluk (Atlantic Salmon (Salmo salar)). Tahapkua naunaipkutaoyot naunaiyaktaohimayot kagitaoyakut ahivaktaokataktot tahapkunanga naunaiyaotaoyonit takkuktaohimayot ahianit unipkangita naunaipkutaitni (Naunaipkutani 3, Naunaipkutani 4, tatvanilo Naunaipkutani 5). Tagiokmi nigginiakviat tahapkua ikaluit pimagioyok; tahapkua ikaluit allatkiit nikkikatiagiakaktot akliyamingnik tatvalu igniugiamingnik hikkukangititlugo. Tatvani unipkami Naunaipkutani 3, naunaiyakhimayatka titigakhugit tahapkua nayogagiloaktaitnik namungaokatakningitiklo tahamani tagiokmi hapkua ikalukpiit ikaluitlo ihuukit hapkua Dolly Varden; kanogitungmangata tahapkua ikaluit nallukhaotaoyut titigakpalialiktitlugo tahamna unipkalioktaoyok, tahapkua ukkikataktot nalliakni kullani uvalunin natkani tahaffuma Kugluk-mik attikaktuk Kuuk. Ikalukpiit nayogagiyakaktot hinnanikhiokhutik takkunakpalangitot ittinikmi uvalunin kikiktani. Tahapkua nayogagikataktait ikaluit ihomagiyaovalangitat nannikatakmangata ukkiumi. Uttigangata tagiokmit tahamunga tattinut immagiktunut ihomanaktok nanikatakmangata ukkiumi, kihianitaok; hapkua ikalukpiit ukkikataktot kulani tahaffuma kukluakviani Kuukmi uttikataktut immagiktunut tattinut pinnagikataktot ikalukpiitnit ukkihimayunit natkanit haffuma kukluakviani Kuukmi, ihomannaktok tatva hivituninga tatvalu ayoknautigikataktat tahamna ingilgayatik mayogahualigangamik kinguvautivagungnakhiyok. Kakugu mayokvikikataktat tattinut immagiktunut pinnagikatakhimayot ukkiuni kinguani tahamna Kuuk hikkunagikatagaluakmat; taima naunaikhimaliktok tatva kakugo mayokvighaat tahapkua ikalukpiit tattinut immagiktunut hillap kannugininganik nayogiyagiakaliktok. Hillap kanogininga pitjutaokatakmat kakugo mayokvighaatnik tahapkua ikalukpiit tatvalu ikaluit ihuukit Dolly Varden nallukhaotaoyut. Tatvani unipkami Naunaipkutani 4, naunaiyaihimayunga kanok tahamna hillap kanogininganik pitjutaokataka tahapkuninga: 1) Kakugo mayokatakat tattinut immagiktunut tahapkua ikalukpiit tatvalu ikaluit ihuukit Dolly Varden; tatvalu, 2) mayokpakhutik kullanut kukluaktup Kuukmi tahapkua ikaluit ihuukit Dolly Varden (naunaiyakhimangitot mayoktunik kullannut Kuukmi huli). Ihomagiluaktavut hilla allangugangat mayokvikhaat tattinut immagiktunut tagiok niklakpalialigangat; tahapkua ikalukpiit mayokataktot tattinut immagiktunut tagiok unnakpaliatitlugo. Tahapkua ikaluit ihuukit ukkikataktot kullani kukluaktumi kuukmi mayokatakmiyot tagiok niklakpalialigangat tahapkuataok ikaluit ihuukit Dolly Varden ukkikataktot natkani tahaffuma kukluaktumi kuukmi. Tahapkua ikaluit ihuukit Dolly Varden ukkikataktot kullani kuukmi, kuukap unnakninga unnatkiyaokatakmat ummilgungnaktokhaoyok mayokpalianiaktitlugit. Immakak tahapkua ikaluit ayughaotigikataktat mayokvikhatik tattinut uttakivagungnakhiyat unnakninganik kukkap. Immaokaomagangat ikkayotaovagungnakhikmiyok kihiani pitjutaovalangituyaaktok mayokvikhaatnik tahapkua ikaluit ihuukit Dolly Varden ukkikataktot kullani kuukmi. Kihianitaok, immaokagangat pitjutaungmiyok mayokvikhaitnik tahapkua ikalukpiit tatvalu ikaluit ihuukit Dolly Varden ukkikataktot natkani kuukmi. taimaitkaluaktitlugit, naunaiyakhimayavut ihomangnaktok tahapkua ikaluit ihuukit Dolly Varden ukkikataktot kullani kukluakviani kuukmi ayoghakhimaitomik mayokataktot tattinut, tatvataok tahapkua ikaluit ukkikataktot natkani kuukmi mayokatakmiyot tattinut immagiktunut kayumiitunuamik. Ikaluit ihuukit Dolly Varden ukkikataktot kullani kukluakviani Kuukmi ahianik tagiop unnakpalianinganik pitjutikakmiyot mayokvighait tattinut immagiktunut immaokaknialo allangangmiyok tahapkunanganin ikaluit ihuukit Dolly Varden tatvanganin ukkikataktunit kullani kukliaviani kuukmi. Ihomanaktok immakak ahianik pitjutikakpagungnakhiyot mayokvikhaat tatvalu/uvalunin ukkiumi namungaovikhaitnik inmingnik ikpigiyakagangamik tahapku tamaita ikaluit taima ihomanaktok. Tahamna Kuuk ikalukaknik atogagiyat tahakmik hapkua ikalukpiit tatvalu ikaluit ihuukit Dolly Varden ukkiukmi natkani tahaffuma Kukluktumi Kuukmi allangayok pitakangituyaakmat tahamna mannigak immak nakingaakmangata illitugingitnamku. Tatvani unipkami naunaipkutani 5-mi, takkukhimayaga kaffiit ihomagivlugit huok ilangit tahapku ikalukpit ukkikatakat natkani tahaffumja kukkiktuk kuukani: igligiyaitlu igniokvigikataktaitniklo naunaiyagahuaklugit, nigginiakvigiyataktaitlo naninmangata tagiokmi, huoklo maayokatangitpat kuukiktumi kuukmit. Tahapkuataok ikaluit ukkiukataktot natkani tahaffuma kuukiktumi kuukmi, takkuhimangitunga hunnanik igginiakatakmangata akkiagoit illuhikangitmata, kihianitaok naunaiyaihimangitnamta ammihunik ikaluknik nannilunin takkukhimangitnaptigo huli. Taima illiitkuhiktuyaaktot tahamaninaakniaktok ukkiugalok naatkani tahaffuma kukluakviani Kuukmi; tahamaniikhatkiyaongmiyot kukkap pannani tatvalu maayoknahaatkiyaovakhutik tatvanganin ikaluit ihuukit Dolly Varden mayoknagikataktot ukkikatakhutik kulani tahaffuma kukluakviani Kuukmi. Tahapkua ikaluit ihuukit Dolly Varden ukkikataktot naatkani kukluakviani Kuukmi ajikingitut ingilgayangit, ilangit tahapkua ikaluit ihuukit ukkikataktot naatkani kukuakviani Kuukmi, ilangitaok ammukatangitot naatkanit haffuma kukluakvianin Kuukmi. Illiitkugingitatka pikagiaghaita igliitnik naatkani tahaffuma kukluakviani Kuukmi tahapkua ikaluit ihuukit uvaluni ikalukpiit. Tahapkua ikaluit naalautait naunaipkutigivlugit illiitugihimayavut ukkikataktutaok ahinni kukkani ilangitni ukkiuni, taima ihomanaktok iglikakpagungnaghiyok tahapkua ikaluit ahinni kukkani tatvalu ukkiyaktokpakhutik tahamunga Kuglumtumi Kuukmit ukkiuni igliliungitagangamik igniukvikhamingnik, ayungnaitkiyaoyungnakhingmat. Tahapkua ikaluit ihuukit Dolly Varden ukkiktaktaktot tahamani naatkani Kuukmi mikitkiyaovakhutik ikalukpiakjuit tatvanganin tahapkuninga ikaluit ihuukitnit Dolly Varden ukkikatakmata kullani tahaffuma kukluakviata Kuukmi, ihomanaktok immakak tahapkua ikaluit ihuukit Dolly ammukpagungnakhiyot kullanut kukluakviani Kuukmi igliliogiaktokhutik igniokvikhamingnik. Igliliokviit tatvalu kanovalaak igliliokatakmangata tammakmik tahapkua allatkik ikaluit nalluyaoyut huli tahamani Kugluktumi Kuukmi. Tahamna naunaiyaktaohimayok unipkalioktaovluni tahapkuninga ikaluit hiitokataktot iliitkuhiitnik ikalukpiit tatvalu hapkua Dolly Varden ikaluit ihuukit nayogagiyat tahamna Kugluktuk Kuukmi, ahiani taima pittakangitok immagiktumik Kuukmik hittuviovaktumik tahapkuninga allatkinguyunik ikalungnik. Ajikiiktoktut tagiokmut hiitovakhutik namungaokatakmangatalo tahapkua ikalukpiit tahapkulo ikaluit ihuukit Dolly Varden tatvalu ammugangata ukkiukhivikhamingnut (kullanut uvalunin natkannut tahaffuma Kuukmi kuukikningani) tahapkua ikaluit ihuukit Dolly Varden ayungnavakniaktot tatva hapkua ikaluknik naunaiyaiyiit havagiyaitnik hivunighami ihomalutaovaliaklikatjuk ikkilivalianingit. Hapkua ikalukpiit tatvalu hapkua ikaluit ihuukit Dolly Varden hiitukataktot Kugluktuni Kuukmit tatvalu tagiokmut Coronation Gulf-mut, uvanga takkukhimayatka tahapkua allatkit ikaluit ajitkingitot hiitugangat ingilgayangit ajikikatangitot ukkiuni. Takkukhimangmiyaga tahamna nuna manigaak hulitjutaongmiyok hittuniahaaktitlugit ikaluit tagiokmut. Taima atjikikatangitmata ikaluit hittuviat namungaukatakniitlo ikkayutaoniakuktat tahapkua ikaluit annaumatjutaitnik hila kannugininganik. Kihiani hivunikhami naunaiyainik pivaligiakaktok naninmangata tahapkua ikaluit igliliokviit tatvalu kannuvaklaak igliliokatakat kaoyivaliotiginahuaklugit kanok hunaniklo ullugiangaktomitjutait tatvalu kanok annaomatjuktikaohighaitnik tahapkua allatkik ikaluit tatvalu tuhaktinahuakutikhaitnik tahapkua ikaluhikinikut ataniktoiyot.
Keywords: Arctic Char; Dolly Varden; life history; migration; Arctic